Spectroscopic identification of geometrical isomers of α- and β-carotenes from palm oil - Tay, Bonnie Yen Ping; Ee, Gwendoline Cheng Lian (Malaysian Palm Oil Board, 2005)
To date, all identification of palm carotenoids are tentative based on electronic absorption spectra, comparison of the elution sequence with past studies and authentic standards. This study reports the isolation of individual major isomers of palm carotenes using a semi-preparative C30 column. The results of MS, 1 H NMR of four isolated peaks, assigned as Fraction 1 (a mixture of 13 and 13’ cis α-carotene), Fraction 2 ( 13 cis β-carotene), Fraction 3 (all trans α-carotene) and Fraction 4 (cis β-carotene) supported the identification of their structures.